Pelatihan Adobe Photoshop untuk Meningkatkan Skill Desain Grafis Pelajar SMK XI DKV Pangeran Antasari - Joko Bintarto; John John; Juli Atika (Nusantara Mengabdi Kepada Negeri, 2026)
This training aims to equip students of to enhance the graphic design skills of students at SMK XI DKV Pangeran Antasari through Adobe Photoshop training. This activity is conducted in response to the growing need for graphic design proficiency among students in the digital age. This service adopts a practical qualitative research method with a direct approach, enabling participants to immediately apply the acquired knowledge. The methods employed include interactive workshops, practical demonstrations, and skills evaluation. The results of the activity demonstrate a significant improvement in students' abilities, with 85% of participants capable of producing simple designs independently. It is therefore expected that upon completion of this training, participants will be able to enhance their creativity in learning, particularly in the field of graphic design, as a primary foundation for becoming professional designers in the workforce."